Kaji Eksperimental Perpindahan Panas Pada Lemari Penyimpan Darah Portable Dengan Memanfaatkan Efek Peltier - Ratna Sary; Amir Zaki Mubarak (Jurnal Teknik Mesin Unsyiah, 2012)
The process of blood storage is the important part in maintaining the blood quality. After it is donated by the donor, the blood will be stored in a storage cabinet until it is needed by the patient. One of the common ways to preserve and maintain the chemical and structural changes of the blood is to store it in a storage area that has a temperature of between 1-6 °C. Blood storage cabinets that already exist this days, use the vapour compression cycle which is only suitable for the storage of large capacity and is not portable if there is blood demand in remote areas. To answer these problems, in this research will be designed and manufactured portable blood storage cabinet by the size of 30 cm x 30 cm x 30 cm. The heat in the storage is discharged to the air by using a heat pump which works using thermoelectric cooler (Peltier effect). The Peltier effect occurs when two metals or semi-conductors of different materials are connected and energized that there will be a difference in temperature. In order to test the feasibility of the blood storage cabinets technically, the heat transfer study is conducted. The experimental result shows that the expected temperature is achieved.